PERKEMBANGAN TEORI MANAJEMEN DARI PEMIKIRAN SCIENTIFIC MANAGEMENT HINGGA ERA MODERN SUATU TINJAUAN PUSTAKA - Isnaeni Rokhayati (Jurnal Ekonomi Dan Bisnis, 2015)
This paper is a review of the literature or a summary of a variety of management science movement of thought  that  emerged  from  the  era  of  the  industrial  revolution,  namely  scientific  management  to today's  modern  era.  The  method  used  in  this  paper  is  a  review  of  the  literature  or  literature  review  with  management  science  thinking.  In  this  study  the  movement  of  thought  in  management  science can be grouped into five areas of thought or theory. This is the fifth thought Scientific Management Theory,  Administrative  Management  Theory,  Behavioral  Management  Theory,  Quantitative Management Theory, and Modern Management Theory. Of its development in the modern era in the management  science    can  also  be  divided  into  three  approaches,  namely  Contingency  approuch (situation  approach),  System  approuch,  and  Dynamic  Engagement  approuch.  The  movement  of thought presented by the emergence of the idea that first appeared and followed another  movement, although in the era of an emerging movement of thought could have another thought. The results of the  study  and  review  of  the  literature  review  of  the  literature  shows  that  the  development  of management  thinking  starts  from  the  idea  of  the  technical  and  productivity  in  manufacturing  and developing the ideas associated with nature and human behavior and the relationship between man and  sisitem  organization.  In  this  paper  the  study  also  found  an  underdeveloped  thoughts  on  the development of business management issues, the management of marketing, financial management, and strategic management.  Keywords  :  development,  Scientific  management  ,  modern  management,  contingency  approach, system approach, dynamic approach to engagement.